Counterinsurgency in Iraq (2003-2006) RAND Counterinsurgency Study--Volume 2 - Pirnie, Bruce R. (RAND Corporation, 2008)
Examines the deleterious effects of the U.S. failure to focus on protecting the Iraqi population for most of the military campaign in Iraq and analyzes the failure of a technologically driven counterinsurgency (COIN) approach. It outlines strategic considerations relative to COIN; presents an overview of the conflict in Iraq; describes implications for future operations; and offers recommendations to improve the U.S. capability to conduct COIN.